Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis

Ialodês et féministes. Réflexions sur l’action politique des femmes noires en Amérique latine et aux Caraïbes - Werneck, Jurema (Nouvelles Questions Féministes, 2005)
Le contexte dans lequel se déroule l’action politique des féministes noires latino-américaines et des Caraïbes est marqué par l’histoire de la colonisation et de l’esclavage. À travers les figures des Ialodês , symboles d’autorité féminine dans certaines cultures africaines, amenées au Brésil notamment au travers des pratiques religieuses, l’autrice montre certains éléments de la pratique politique des femmes afro-descendantes qui précèdent le féminisme théorique, créé en Occident. Elle critique le féminisme latino-américain et des Caraïbes, influencé par celui d’Europe et des États-Unis, notamment pour son caractère excluant, du fait de sa vision classiste et raciste, tout en reprenant certain de ses apports. Werneck critique par ailleurs la politique d’identité pratiquée par une grande partie du mouvement de femmes afro-descendantes, qu’elle considère insuffisant pour permettre la mobilisation politique, pourtant nécessaire face à la mondialisation économique et les nouveaux contextes historiques. Elle présente ainsi de nouveaux défis au mouvement social anti-raciste et anti-sexiste.
Keywords: afro-féminisme; amérique latine; amériques; approches et analyses; caraïbes; cours; discours dominant; fem3300; féminisme afroaméricain; féminisme décolonial; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions